2020
DOI: 10.1016/j.bone.2020.115227
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based assessment of proximal femur strength compared to mechanical testing

Abstract: Half of the women who sustain a hip fracture would not qualify for osteoporosis treatment based on current DXA-estimated bone mineral density criteria. Therefore, a better approach is needed to determine if an individual is at risk of hip fracture from a fall. The objective of this study was to determine the association between radiation-free MRI-derived bone strength and strain simulations compared to results from direct mechanical testing of cadaveric femora.Imaging was conducted on a 3-Tesla MRI scanner usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…[65][66][67] In this regard, FEA applied to MRI data has shown to be a promising approach that can reliably provide fracture risk information and evaluation of bone strength with good reproducibility of FEA measurements, furthermore pointing at good agreement of the method against the gold standard of mechanical testing at the femur. 47,[68][69][70]…”
Section: Technical Principlesmentioning
confidence: 99%
“…[65][66][67] In this regard, FEA applied to MRI data has shown to be a promising approach that can reliably provide fracture risk information and evaluation of bone strength with good reproducibility of FEA measurements, furthermore pointing at good agreement of the method against the gold standard of mechanical testing at the femur. 47,[68][69][70]…”
Section: Technical Principlesmentioning
confidence: 99%
“…However, we used the same modeling approach as others 7,10,15 . A recent cadaver study demonstrated high consistency between experimentally measured and MRI‐FEA derived bone strength (and stiffness) of the proximal femur given a sideways loading configuration, strongly supporting the use of MRI‐FEA to reliably predict the mechanical competence of the human femur in clinical settings 14 . Second, due to limitations of computational resources, only linear elastic FEA was conducted and our results are thus limited to reports of whole‐bone stiffness and high‐risk tissue strains.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, we speculate that the anisotropic feature of the elements might have limited effect on the overall mechanical performance of the proximal femur. Indeed, a recent cadaver study has shown strong agreements between experimentally measured values of the femoral stiffness (and strength) and predictions from both isotropic and anisotropic voxel‐based MRI‐FE models 14 …”
Section: Discussionmentioning
confidence: 96%
“…These studies highlight the usefulness of FEA derived from micro-MRI for monitoring treatment response. FEA using specialised MRI algorithms have been validated for the distal tibia ( Rajapakse et al, 2018 ) and more recently for the femur ( Rajapakse and Chang, 2018 ; Rajapakse et al, 2020 ). FEA of the femur is especially useful for evaluating fracture risk in the hip as it can simulate forces experienced during a sideways fall, which accounts for the main orientation in which hip fractures occur ( Keyak et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%